Terapi Latihan Aerobik untuk Menurunkan Tekanan Intraokular (TIO) sebagai Pencegahan Glaukoma : Literature Review - Maulidya Yuniar Rahmawati; Siswoyo Siswoyo; Ana Nistiandani; Kushariyadi Kushariyadi (Bima Nursing Journal, 2022)
Introduction: High IOP causes disturbing retinal ganglion cell axons’s work in sending impulses and causes visual disturbances. Restrictions on non-urgent health services due to Covid-19 pandemic caused telehealth treatments be carried out so physical examinations such as IOP measurements couldn’t be carried out, even though IOP control was important to keep visual field from narrowing. Method: Databases used: Google Scholar, PubMed, Research Gate, Science Direct, Wiley One Library, Sage Journals, Springer, Nature, Emerald, Cambridge Core, and ProQuest. Keywords entered into database, articles filtered according to inclusion criteria. Articles tested with JBI critical, and analyzed if score was >50%. Result: 7 articles mentioned a significant decrease in IOP, 1 article mentioned a non-significant decrease in IOP, and 2 articles mentioned an increase in duration and frequency of exercise associated with decrease in baseline IOP. Analysis: Aerobic exercise can reduce IOP immediately after exercise up to ±30 minutes. Although it’s temporary but if it’s done continuously it can reduce the baseline of IOP. The decrease in IOP was due to jogging on track 4.3mmHg, jogging on treadmill 3.0mmhg, running on ergometer bicycle 2.7mmhg, and running on treadmill 2.12-2.60mmHg. Conclusion: Jogging on track can lower IOP the most compared to other types of aerobic exercise.